2015
DOI: 10.1097/md.0000000000002023
|View full text |Cite
|
Sign up to set email alerts
|

Serum TRSUT Titer ≥1

Abstract: Supplemental Digital Content is available in the text

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 25 publications
2
6
0
Order By: Relevance
“…Jiang et al ( 36 ) indicated that among HIV-negative patients, those with serum-TRUST titers ≥1:16 have a higher probability of developing NS. The present study confirmed that age and the serum TRUST titer were risk factors for NS, which is in accordance with previous studies ( 37 ). A serum TRUST titer ≥1:8 with 79.3% sensitivity and 87.5% specificity was a strong predictor of NS.…”
Section: Discussionsupporting
confidence: 94%
“…Jiang et al ( 36 ) indicated that among HIV-negative patients, those with serum-TRUST titers ≥1:16 have a higher probability of developing NS. The present study confirmed that age and the serum TRUST titer were risk factors for NS, which is in accordance with previous studies ( 37 ). A serum TRUST titer ≥1:8 with 79.3% sensitivity and 87.5% specificity was a strong predictor of NS.…”
Section: Discussionsupporting
confidence: 94%
“…In the present study, as the serum RPR titers gradually increased, we observed a rising trend in the likelihood of S-NS in HIV-negative patients, which coincided with a previous study of HIV-infected neurosyphilis patients [ 15 ]. In syphilis patients co-infected with HIV, serum RPR titers of 1:32 or 1:16 were recommended as indicators to determine the need for lumbar punctures in patients without neurological symptoms [ 9 , 15 ]. However, among our HIV-negative subjects with neurological symptoms, a titer of 1:4 was found to be the optimal cut-off point to recognize S-NS, with a sensitivity of 76.6%.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on neurosyphilis were confined to demographic characteristics, stage of syphilis, serum RPR titer and profiles of HIV infection [ 4 , 6 , 9 ]. In this study, we took the comorbidities and biochemical parameters into consideration and found that serum CK could aid in the recognition of both confirmed and probable neurosyphilis.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, increased serum/CSF TRUST titer, which is ≥1:16, is consistent with previous studies. [ 23 , 24 ]…”
Section: Discussionmentioning
confidence: 99%